OPPORTUNITIES AND RISKS OF AI INTEGRATION INTO THE EDUCATIONAL PROCESS - Otakuziev Sardorbek (“SUN’IY INTELLEKTNING TIL O‘RGANISHDAGI O‘RNI” MAVZUSIDA TALABALAR ILMIY-AMALIY KONFERENSIYASI, 2025)
This article examines the opportunities and risks of integrating artificial intelligence (AI) into education. It outlines how AI can support independent learning, improve assessment, enhance language acquisition, and assist students with special needs via virtual mentors and chatbots. While AI offers improved accessibility and efficiency, challenges remain—such as its inability to provide emotional support and the risk of cognitive overload. The article emphasizes that to ensure effective and inclusive education, a balance between AI and human interaction is essential.